2019
DOI: 10.1002/cbin.11136
|View full text |Cite
|
Sign up to set email alerts
|

Let‐7b‐5p inhibits proliferation and motility in squamous cell carcinoma cells through negative modulation of KIAA1377

Abstract: KIAA1377 has been found to be linked with lymph node metastasis in esophageal squamous cell carcinoma (SCC) in our previous study; however, the regulation of KIAA1377 remains far from understood. Herein, to understand the regulation of KIAA1377 from the angle of microRNA (miRNA)–messenger RNA (mRNA) modulation in the setting of SCC cells, the basal level of KIAA1377 was determined by quantitative real‐time polymerase chain reaction (qRT‐PCR) and western blot analysis in KYSE‐150 and HeLa cells; biological role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Let-7b-5p has been reported to play an anticancer role in many cancers. [41][42][43] However, the biological function of let-7b-5p in HCC was still unclear. We overexpressed let-7b-5p in HuH7 and Hep3B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Let-7b-5p has been reported to play an anticancer role in many cancers. [41][42][43] However, the biological function of let-7b-5p in HCC was still unclear. We overexpressed let-7b-5p in HuH7 and Hep3B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Zheng et al explained that let-7b-5p suppressed cell proliferative and migratory abilities in squamous cell carcinoma. 16 Let-7b-5p was also reported to participate in endoplasmic reticulum (ER) stress response in acute pulmonary embolism. 17 In this study, we found LINC00987 contained the putative binding sites of let-7b-5p, suggesting that LINC00987 might regulate COPD progression by sponging let-7b-5p.…”
Section: Introductionmentioning
confidence: 99%
“…There have been extensive studies of let-7b-5p in the context of cancer, suggesting that let-7b-5p is a tumor-suppressor miRNA and potential diagnostic biomarker [ 8 , 9 ]. Moreover, Yu et al revealed that let-7b-5p was upregulated in neonatal leukocytes with LPS stimulation derived from cord blood of infants [ 10 ].…”
Section: Introductionmentioning
confidence: 99%